2022
DOI: 10.21037/atm-22-180
|View full text |Cite
|
Sign up to set email alerts
|

BATF2 and PDK4 as diagnostic molecular markers of sarcoidosis and their relationship with immune infiltration

Abstract: Background: Sarcoidosis (SA) is an immune disorder disease featuring granulomas formation with a controversial etiopathogenesis. We aimed to uncover potential markers for SA diagnosis and explore how immune cell infiltration contributes to the pathogenesis of SA.Methods: Sarcoidosis GSE83456 samples and GSE42834 from Gene Expression Omnibus (GEO) were analyzed as the training and external validation sets, respectively. Firstly, R statistical software was employed to uncover the differentially expressed genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Overall, results from 11 different cohorts of whole blood, PBMC, BAL cells, and lung tissue supported the diagnostic efficacy of the essential genes, with the splendid AUCs ranging from 0.938 to 1.000 in training datasets and ranging from 0.728 to 0.972 in validation datasets. He J et al found that BATF2 and PDK4 could be used as diagnostic molecular markers for sarcoidosis through bioinformatics approaches in two cohorts (35). Our SARDS model, which combined the construction and validation of 11 cohorts, had higher diagnostic efficacy than other diagnostic models, further validating that SARDS was feasible and reliable in diagnosing patients with sarcoidosis.…”
Section: Discussionsupporting
confidence: 54%
“…Overall, results from 11 different cohorts of whole blood, PBMC, BAL cells, and lung tissue supported the diagnostic efficacy of the essential genes, with the splendid AUCs ranging from 0.938 to 1.000 in training datasets and ranging from 0.728 to 0.972 in validation datasets. He J et al found that BATF2 and PDK4 could be used as diagnostic molecular markers for sarcoidosis through bioinformatics approaches in two cohorts (35). Our SARDS model, which combined the construction and validation of 11 cohorts, had higher diagnostic efficacy than other diagnostic models, further validating that SARDS was feasible and reliable in diagnosing patients with sarcoidosis.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, BATF2 plays a critical role in the infiltration of immune cells and inflammation in sarcoidosis, a chronic disease associated with granuloma formation. 14 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…MPO (myeloperoxidase) [778] participated in the regulation of mixed connective tissue disease progression. Enriched genes including MPO (myeloperoxidase) [779], CXCL11 [780], IL1A [781], CXCL10 [782], FCGR3B [783], IL1B [784], TTN (titin) [300], BATF2 [785], VIP (vasoactive intestinal peptide) [786], TLR3 [787], CCR2 [788], TLR7 [789], and CR1 [790] wereclosely related to sarcoidosis. A study indicates that enriched genes including MPO (myeloperoxidase) [791], RXFP1 [792], CXCL11 [793], CTNND2 [615], BMPR2 [794], TLR3 [795], CCR2 [796], and CAV1 [797] are altered expressed in scleroderma.…”
Section: Discussionmentioning
confidence: 99%